2017
DOI: 10.1158/1538-7445.am2017-784
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 784: Pharmacodynamic biomarkers in metronomic chemotherapy: Multiplex cytokine measurements in gastrointestinal cancer patients

Abstract: Metronomic chemotherapy has shown promising antitumor activity in a number of malignancies. For example, we previously reported (Allegrini et al., Angiogenesis (2012) 15(2):275-86) a phase II clinical trial of metronomic UFT (a 5-fluorouracil prodrug; 100 mg/twice per day p.o.) and cyclophosphamide (CTX; 500 mg/mq2 i.v. bolus on day 1 and then 50 mg/day p.o.) plus celecoxib (200 mg/twice a day p.o.) in 38 patients with advanced refractory gastrointestinal tumors. The mechanisms of action of metronomic chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For the data of an immune system multiplex 14-cytokine profiling of plasma samples available from 31 patients with advanced refractory gastrointestinal tumors [ 8 , 11 ] ([V alenzuela P et al. , S ubmitted ), we showed that the scores derived from the suitably chosen combinations of three biomarkers has a classification power comparable to the RECIST criteria clinical classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the data of an immune system multiplex 14-cytokine profiling of plasma samples available from 31 patients with advanced refractory gastrointestinal tumors [ 8 , 11 ] ([V alenzuela P et al. , S ubmitted ), we showed that the scores derived from the suitably chosen combinations of three biomarkers has a classification power comparable to the RECIST criteria clinical classification.…”
Section: Discussionmentioning
confidence: 99%
“…plus celecoxib [ 8 ]. Experimental details as well as a discussion on the implications of cytokines levels for understanding the mechanism of action of metronomic therapy are provided elsewhere [ 8 , 11 , V alenzuela P et al. , S ubmitted ].…”
Section: Methodsmentioning
confidence: 99%
“…Efforts should focus on conducting large prospective trials (Table 1) [31] (ideally phase-III trials) incorporating MTC alone or in combination with synergetic drugs, to attain high-quality evidence supporting its use, specifically in earlier treatment settings [32]. It is important to identify patient-subpopulations for whom MTC would be best and establish the ideal predictive biomarkers that correlate with clinical outcomes [33]. Broader awareness of the potential of MTC should be acknowledged, with more investigations implemented in pursuit of the integration of MTC in cancer treatment algorithms.…”
Section: Expert Opinionmentioning
confidence: 99%